2018
DOI: 10.22331/q-2018-05-22-65
|View full text |Cite
|
Sign up to set email alerts
|

Anticoncentration theorems for schemes showing a quantum speedup

Abstract: One of the main milestones in quantum information science is to realise quantum devices that exhibit an exponential computational advantage over classical ones without being universal quantum computers, a state of affairs dubbed quantum speedup, or sometimes "quantum computational supremacy". The known schemes heavily rely on mathematical assumptions that are plausible but unproven, prominently results on anticoncentration of random prescriptions. In this work, we aim at closing the gap by proving two anticonc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 69 publications
(156 reference statements)
0
85
0
Order By: Relevance
“…For the case of the random universal circuits of Ref. [15] there is evidence that the output distribution of fixed instances is essentially given by an exponential (Porter-Thomas) distribution P PT whose second moment is given by [20,Eq. (8)]…”
Section: B Universal Random Circuits and Spherical 2-designsmentioning
confidence: 99%
“…For the case of the random universal circuits of Ref. [15] there is evidence that the output distribution of fixed instances is essentially given by an exponential (Porter-Thomas) distribution P PT whose second moment is given by [20,Eq. (8)]…”
Section: B Universal Random Circuits and Spherical 2-designsmentioning
confidence: 99%
“…The gates used in these circuits are from {CZ, X 1/2 , Y 1/2 , T }. In [17] it is shown that circuits from this set anticoncentrate if they are chosen as follows: let G = {CZ, X 1/2 , X −1/2 , Y 1/2 , Y −1/2 , T, T † } (i.e. the previous set closed under inverses).…”
Section: Random Circuit Sampling [4]mentioning
confidence: 99%
“…This result has been shown in the recent works [6] and [24] (and our results were developed independently concurrently) but only for a single particular hardness conjecture. Furthermore both papers prove the anticoncentration conjecture by using the fact that random Clifford circuits form a k-design for suitable k. The idea of using k-designs to prove anticoncentration conjectures is explored in [17]. In this paper, we use a different approach.…”
Section: Introductionmentioning
confidence: 99%
“…By magic state injection, circuits with this gate set can be efficiently simulated by Clifford circuits with magic state |T inputs, where |T = 1 √ 2 (|0 + e iπ/4 |1 ). It has been shown that postCM = postBQP [13], and thus output probabilities are #P-hard approximate up to some constant relative error [24][25][26]. However, if there is some independent depolarizing error acting on each input magic state, e.g., the input state on each register is (1 − ε)|T T | + ε I 2 , then Theorem 1 implies directly that there exists a classical algorithm to approximate the output probability up to l 1 norm δ in time n O(log(1/δ )/ε) for a large fraction of the CM circuits with noisy inputs.…”
Section: A Mixed Input Statesmentioning
confidence: 99%